PENGARUH LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA SALESFORCE YANG DIMEDIASI OLEH PENGEMBANGAN KARIR - Nurrul Tiara Dinni; Tjiptogoro Dinarjo Soehari (Akademika, 2020)
This study aims to examine and analyze career development as mediator of work environment and organizational commitment on salesforce performance at PT. Astra International Tbk - Daihatsu Sales Operation Wil. DKI 2. This study uses a quantitative approach with structural equation model or SEM through software named PLS (Partial Least Square) method with the smartPLS program. The population of the study is numbered 344 and sampling using non-probability (purposive sampling) in which employee criteria as Salesforce at PT. Astra International Tbk - Daihatsu Sales Operation Wil. DKI 2 (consists of 20 branches), therefore sample obtained is numbered 185 respondents. The model theory used is showing fit to empirical data. The results of study showed that: (1) work environment has no significant effect on salesforce performance, (2) organizational commitment has a positive and significant on salesforce performance, (3) work environment has a positive and significant on development career, (4) organizational commitment has a positive and significant on development career, (5) career development has a positive and significant on salesforce performance, (6) work environment has a positive and significant on salesforce performance with development career as full mediator, (7) and organizational commitment has a positive and significant on salesforce performance with career development as partial mediator.